Improving Elementary Students' Motivation and IPAS Learning Outcomes through a Wordwall-Based Team Games Tournament Model - Andika Wahyu Hanusa Bhakti; Sudarmiani Sudarmiani; Ibadullah Malawi (Journal of General Education and Humanities, 2026)
Conventional IPAS learning often yields low motivation and poor outcomes due to passive methods, while integrating digital games with cooperative models remains underexplored. This study aims to describe the implementation of the Wordwall-assisted Team Games Tournament (TGT) model and to determine improvements in motivation and IPAS learning outcomes among fifth-grade students. Employing Classroom Action Research with qualitative and quantitative descriptive data, the study involved 22 students over two cycles. Data were collected through observation, testing, and documentation. The success criteria were set at a minimum 61% class motivation and 80% classical mastery. The results indicate that: (1) the TGT-Wordwall model created active and interactive learning through digital tournaments; (2) learning motivation increased from 40% (pre-cycle) to 49% (Cycle I) and 72% (Cycle II); and (3) average learning outcomes rose from 65.27 to 70.18 and 79.09, with classical mastery reaching 41%, 64%, and 86%, respectively, exceeding the 80% target. The findings indicate that the Wordwall-assisted Team Games Tournament model can support improvements in students' motivation and IPAS learning outcomes. The integration effectively transforms passive classrooms into active, collaborative environments. This provides a practical, technology-enhanced framework for elementary educators to boost both affective and cognitive domains in learning.